Human capital, capital goods import and economic growth in West Africa - Raphael Kolade Ayeni; Kemi Funlayo Akeju (Cogent Economics & Finance, 2023)
This research paper investigates interactions of human capital, capital goods import and economic growth with a panel of 13 West African countries comprises of 7 low income and 6 low-middle income countries over the period of 1980-2018. The study adopts the Panel Auto-Regressive Distributed Lag (ARDL) cointegration techniques to establish a short and long-run relationship existing among the variables. Panel ARDL (Fixed effect) result revealed that the returns to equipment investment are moderately high on the average. Findings do not support the hypothesis that human capital makes production inputs more effective and helps countries gain from equipment investment and other imported investment for all the countries. This is due to inadequate knowhow and skill arising from the low levels of human capital in these countries. Determining the threshold of human capital development at which countries benefit from equipment investment, findings indicates that countries of the low-middle Income that exhibit a comparatively higher human capital (1.45 on the average) benefited more from imported capital stock and other importations than countries of the low income with very low human capital (1.27 on the average). Thus, we conclude that investment in human capital, innovation, and knowledge are significant contributors to economic growth and should be the priority of developing economies.
Keywords: 330; capital stock import; economic growth; human capital; low income countries; low-middle income countries; panel auto-regressive distributed lag model